2021
DOI: 10.1186/s13039-021-00552-3
|View full text |Cite
|
Sign up to set email alerts
|

Inherited unbalanced translocation (4p16.3p15.32 duplication/8p23.3p23.2deletion) in the four generation pedigree with intellectual disability/developmental delay

Abstract: Chromosomal copy number variants (CNVs) are an important cause of congenital malformations and mental retardation. This study reported a large Chinese pedigree (4-generation, 76 members) with mental retardation caused by chromosome microduplication/microdeletion. There were 10 affected individuals with intellectual disability (ID), developmental delay (DD), and language delay phenotypes. SNP array analysis was performed in the proband and eight patients and found all of them had a microduplication of chromosom… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 29 publications
0
2
0
Order By: Relevance
“…Chromosomal abnormalities, including duplications, deletions, and Fragile X syndrome, were prevalent, underlining the significance of genomic examinations in diagnosing growth, developmental, and congenital anomalies [21,22] . The study highlighted the association of dysmorphic features, epilepsy, family history, and ID level with positive parental consanguinity, though a significant association was not established, likely due to the small sample size [23,24] . The research found that duplications were mostly associated with mild ID and consanguinity, similar to findings of deletions and brain atrophy [25] .…”
Section: Discussionmentioning
confidence: 86%
“…Chromosomal abnormalities, including duplications, deletions, and Fragile X syndrome, were prevalent, underlining the significance of genomic examinations in diagnosing growth, developmental, and congenital anomalies [21,22] . The study highlighted the association of dysmorphic features, epilepsy, family history, and ID level with positive parental consanguinity, though a significant association was not established, likely due to the small sample size [23,24] . The research found that duplications were mostly associated with mild ID and consanguinity, similar to findings of deletions and brain atrophy [25] .…”
Section: Discussionmentioning
confidence: 86%
“…Anomalies have been reported affecting the brain (ventriculomegaly, cortical atrophy and prominent ventricles, large occipital encephalocele) [12][13][14], eyes (bilateral hypermetropia, pigmentary retinal degeneration, microphthalmia) [15][16][17][18], cleft palate and Pierre Robin syndrome [3,5,7,[19][20][21], heart (enlarged right atrium and ventricle, small atrial septal defect, abnormal structure and function of both ventricles and double inferior vena cava, coarctation of the aorta and interventricular communication, both valvar pulmonic stenosis, cor triatriatum) [3,8,[22][23][24], kidneys (duplicated left intrarenal collecting system, polycystic kidney, bilateral extrarenal pelvis dysplastic cystic kidneys) [3, 9, 24-26], genital defects [27], limb development disorder (irregularity of the outline of the distal phalanx of the 4th digit, rudimentary left thumb with absence of right thumb, bilateral absence of ulna) [28][29][30][31]. Craniofacial dysmorphism has frequently been reported with signs that are not speci cally diagnostic [32][33][34][35][36], as well cognitive involvement [17,[37][38][39][40][41], de cit of growth [25,34] and epileptic seizures [22,25]. Other reported anomalies include congenital hearing impairment [18, 42], hypercalciuria and kidney calci cation [43], familial combined hyperlipidemia <...…”
Section: Discussionmentioning
confidence: 99%